Effects of pathogen infection and Rhizobium inoculation on instantaneous and long-term water use efficiency of peanut with and without drought - Regassa, Girmaye Benti; Zhang, Yuxian; Shen, Yifan; Zhang, Liwei; Zhang, Jiating; Liu, Yinzhan; Li, Guoyong; Xiao, Rui; Yang, Zhongling (Frontiers in Microbiology, 2025)
IntroductionWater Use Efficiency (WUE) is one of the critical indicators to characterize plant adaptation to arid environments, however, the effects of pathogens infection and Rhizobium symbiosis on WUE are not considered in contexts of water stress.MethodsA study was conducted in a greenhouse pot to examine the effects of changed soil water conditions on instantaneous Water Use Efficiency (WUEi) and long-term Water Use Efficiency (WUEL) under inoculation Rhizobium, inoculation Fusarium sp., and co-inoculation Rhizobium and Fusarium sp.ResultsThe results showed that inoculation Fusarium sp. and co-inoculation Rhizobium and Fusarium sp. reduced WUEi by increasing net photosynthetic rate without drought. Inoculation Fusarium sp. and co-inoculation Rhizobium and Fusarium sp. reduced WUEi by decreasing plant height with drought. Inoculation Rhizobium and Fusarium sp. significantly reduced WUEL by lowering intercellular CO2 concentration without drought. Inoculation Rhizobium reduced WUEL by increasing root nodule number with drought. In contrast, drought had no effect on either WUEi or WUEL without inoculation.DiscussionThe results suggest that Fusarium sp. infection is detrimental to instantaneous Water Use Efficiency while inoculation Rhizobium is unfavorable to long-term Water Use Efficiency, regardless of drought effects. Our findings provide a new insight for developing effective water use strategies after pathogen infection or Rhizobium symbiosis under increased precipitation scenarios.